2006
DOI: 10.1128/jb.188.2.515-524.2006
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of the Myxococcus xanthus Ω4406 Promoter Region Reveals an Upstream Negative Regulatory Element That Mediates C-Signal Dependence

Abstract: C signaling plays a key role in coordinating cell movement and differentiation during the multicellular developmental process of Myxococcus xanthus. C signaling regulates expression of genes induced after about 6 h into development, when cells are forming mounds. One gene whose expression depends absolutely on C signaling was identified by insertion of a transposable element at site ⍀4406 which generated a transcriptional fusion between lacZ and an upstream promoter. We have investigated regulation of the ⍀440… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 45 publications
2
20
0
Order By: Relevance
“…7). The inhibitory effect of the 0.8-kb segment on developmental lacZ expression from fusions integrated at Mx8 attB has also been demonstrated with a vector (pREG1727) bearing a Km r gene (55). In contrast, the 0.8-kb segment does not inhibit developmental expression of lacZ from fusions integrated by homologous recombination at the native ⍀4406 site (Fig.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…7). The inhibitory effect of the 0.8-kb segment on developmental lacZ expression from fusions integrated at Mx8 attB has also been demonstrated with a vector (pREG1727) bearing a Km r gene (55). In contrast, the 0.8-kb segment does not inhibit developmental expression of lacZ from fusions integrated by homologous recombination at the native ⍀4406 site (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…5) precisely localized the 5Ј end. Mutational analysis has confirmed that the 5Ј end reflects the transcriptional start site of the ⍀4406 promoter (55). However, we discovered that expression of a lacZ reporter fused transcriptionally to the ⍀4406 promoter depends strongly on the position of the fusion in the M. xanthus chromosome.…”
Section: Discussionmentioning
confidence: 94%
“…The cis-regulatory element to which MrpC2 binds in the fmgA promoter region includes a 5-bp element and a C box. These 2 sequences are similarly arranged upstream of other C-signal-dependent promoters and are important for promoter activity (21)(22)(23), suggesting that MrpC2 may bind to these sites. Indeed, in the promoter region of the operon identified by Tn5 lac ⍀4499 (22), MrpC2 binds near a 5-bp element, and in combination with FruA, formation of shifted complexes in EMSAs is greatly enhanced (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…1A) (18), and subsequent analysis showed that the FruA DNA-binding domain (FruA-DBD) binds to the sequence between Ϫ86 and Ϫ77 (17). The sequence between Ϫ63 and Ϫ46 contains 2 elements found in other C-signal-dependent promoter regions; a 5-bp element (consensus GAACA) and a C box (consensus CAYYCCY; Y means C or T) (21)(22)(23). Mutations in this region nearly abolish fmgA promoter activity ( Fig.…”
mentioning
confidence: 99%
“…The finding that MrpC2 and FruA bind cooperatively to crucial cis-regulatory sequences upstream of the fmgA promoter suggests that these transcription factors coordinate starvation signaling and cell death with positional information via short-range C-signaling to govern gene expression and cell fate during M. xanthus development (35). This novel mechanism of fmgA combinatorial control was predicted to be conserved because similar cis-regulatory sequences have been found upstream of other developmentally regulated M. xanthus promoters (6,31,52,(59)(60)(61)67).…”
mentioning
confidence: 97%